Handbook of nanofabrication - Wiederrecht, Gary P. (Elsevier, 2010)
Many of the devices and systems used in modern industry are becoming progressively smaller and have reached the nanoscale domain. Nanofabrication aims at building nanoscale structures, which can act as components, devices, or systems, in large quantities at potentially low cost. Nanofabrication is vital to all nanotechnology fields, especially for the realization of nanotechnology that involves the traditional areas across engineering and science. Includes chapters covering the most important Nanofabrication techniques, which aids comprehensive understanding of the latest.